Glass Transition Behaviour of PMMA/PVA Incompatible Blend. Issue 6 (July 2013) - Nakamura, Yoshinobu; Kariya, Eiji; Fukuda, Tomoyoshi; Fujii, Syuji; Fujiwara, Kazuko; Hikasa, Shigeki
Dynamic viscoelastic properties and morphology of poly(methyl methacrylate) (PMMA)/poly(vinyl alcohol) (PVA) blend prepared by melt kneading was investigated. These solubility parameter values differ greatly. Two kinds of PVA with saponification degrees of 88 and 98 mol.% were used. Micrometre-order domains were observed by scanning electron microscopy for 88 mol.% PVA, whereas no clear domain was observed for 98 mol.%. Both the blends were incompatible systems because two loss modulus peaks based on PMMA and PVA were observed by dynamic mechanical analysis. The loss modulus peak based on the PMMA-rich phase was higher than that of pure PMMA; the increase of the corresponding glass transition temperature (Tg ) caused by blending was more remarkable for 98 mol.% PVA than 88 mol.%. It was thought that the intermolecular interaction of OH group in PVA and carbonyl group in PMMA caused the increase in Tg, but no clear evidence of the interaction for the blend was observed by a Fourier transform infrared spectroscopic analysis. The poly(vinyl acetate)/PMMA blend was incompatible. The unsaponificated vinyl acetate unit in PVA decreased the interaction between PMMA and PVA. This is the reason why the effect of Tg rising was lower for 88 mol.% PVA than for 98 mol.%.